2006
DOI: 10.1016/j.otohns.2005.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Type 3 Portable Monitoring in Unattended Home Setting for Suspected Sleep Apnea: Factors That May Affect its Accuracy

Abstract: Type 3 PM is feasible in unattended home-setting for routine examination. Influence of the factors above should be comprehensively considered especially for mild patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 19 publications
6
45
0
4
Order By: Relevance
“…67,86 Seven studies evaluated the performance of Type 3 HSAT devices against PSG, but the AHI cutoffs employed varied across studies, resulting in sub-grouping by AHI cutoffs for our analyses. [87][88][89][90][91][92][93] When using an AHI ≥ 5 cutoff, accuracy in a high-risk population (assuming a prevalence of 87%) ranged from 84% to 91%, whereas in a low-risk population (assuming a prevalence of 55%) accuracy ranged from 70% to 78% based on the seven studies (see supplemental material, Table S39). Using a cutoff of AHI ≥ 15, the accuracy of these devices in a high-risk population ranged from 65% to 91%, based on six studies 87,[89][90][91][92]94 (see supplemental material, Table S40).…”
Section: Accuracymentioning
confidence: 99%
“…67,86 Seven studies evaluated the performance of Type 3 HSAT devices against PSG, but the AHI cutoffs employed varied across studies, resulting in sub-grouping by AHI cutoffs for our analyses. [87][88][89][90][91][92][93] When using an AHI ≥ 5 cutoff, accuracy in a high-risk population (assuming a prevalence of 87%) ranged from 84% to 91%, whereas in a low-risk population (assuming a prevalence of 55%) accuracy ranged from 70% to 78% based on the seven studies (see supplemental material, Table S39). Using a cutoff of AHI ≥ 15, the accuracy of these devices in a high-risk population ranged from 65% to 91%, based on six studies 87,[89][90][91][92]94 (see supplemental material, Table S40).…”
Section: Accuracymentioning
confidence: 99%
“…[46][47][48]52,55,81,88,89,98,104 In addition, 7 of 14 inlaboratory studies showed a decline in sensitivity and an increase in specificity, and 2 studies showed an increase in area under the ROC curve. 47,48,51,52,58,[61][62][63][65][66][67][69][70][71] We found no significant difference in baseline characteristics between the 2 groups of patients in all 8 studies that reported disease management after the diagnosis by either test.…”
Section: Diagnostic Accuracy Of Sleep Testsmentioning
confidence: 99%
“…Inlaboratory PSG is also not practical in some situations, such as postoperative sleep evaluation. To deal with this issue, a number of portable sleep monitoring devices have been developed [15][16][17][18][19][20]. To provide evidence-based recommendations on the use of unattended portable monitors in the diagnosis of obstructive sleep apnea in adult patients, a clinical guideline has been published by the Portable Monitoring Task Force of the American Academy of Sleep Medicine in 2007 [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%